Avoiding errors in the diagnosis of polypoidal choroidal vasculopathy in patients with age-related macular degeneration (Part 1) (Ukrainian Journal of Ophthalmology, 2025)
Background: Poor availability of indocyanine green angiography (ICGA) raises the question of how to improve the diagnosis of polypoidal choroidal vasculopathy (PCV) using alternative imaging modalities, optical coherence tomography (OCT) and OCR angiography (OCTA).Purpose: To optimize the diagnosis of PCV in patients with age-related macular degeneration (AMD) using non-invasive methods, OCT and OCTA.Material and Methods: One hundred and sixty-nine patients (228 eyes) with neovascular AMD underwent OCT and OCTA study as per the proposed algorithm to differentiate between PCV and other types of subretinal neovascularization. Of these, 14 patients (8.28%; 14 eyes) were found to have PCV.Results: Major and additional signs of PCV, secondary neovascularization and activity of the process on OCT were determined. In addition, we determined the signs of PCV on OCTA manu-al and automatic segmentation which will be helpful in accurate differential diagnosis of the disease. On the basis of these data, we developed a step-by-step algorithm of the OCT and OC-TA diagnosis of PCV in patients suspected of the disease, which allows the accurate diagnosis when ICGA is unavailable.Conclusion: Systematic step-by-step interpretation of OCT and OCTA scans allow the reliable differential diagnosis of PCV in patients with exudative AMD.
Keywords: optical coherence tomography; optical coherence tomography angiography; age-related macular degeneration; polypoidal choroidal vasculopathy; differential diagnosis